Proteasome impairment in neural cells derived from HMSN-P patient iPSCs. Issue 1 (December 2017) - Murakami, Nagahisa; Imamura, Keiko; Izumi, Yuishin; Egawa, Naohiro; Tsukita, Kayoko; Enami, Takako; Yamamoto, Takuya; Kawarai, Toshitaka; Kaji, Ryuji; Inoue, Haruhisa
Abstract Hereditary motor and sensory neuropathy with proximal dominant involvement (HMSN-P) is caused by a heterozygous mutation (P285L) inTropomyosin-receptor kinase Fused Gene (TFG ), histopathologically characterized by progressive spinal motor neuron loss with TFG cytosolic aggregates. Although the TFG protein, found as a type of fusion oncoprotein, is known to facilitate vesicle transport from endoplasmic reticulum (ER) to Golgi apparatus at ER exit site, it is unclear how mutant TFG causes motor neuron degeneration. Here we generated induced pluripotent stem cells (iPSCs) from HMSN-P patients, and differentiated the iPSCs into neural cells with spinal motor neurons (iPS-MNs). We found that HMSN-P patient iPS-MNs exhibited ubiquitin proteasome system (UPS) impairment, and HMSN-P patient iPS-MNs were vulnerable to UPS inhibitory stress. Gene correction of the mutation inTFG using the CRISPR-Cas9 system reverted the cellular phenotypes of HMSN-P patient iPS-MNs. Collectively, these results suggest that our cellular model with defects in cellular integrity including UPS impairments may lead to identification of pathomechanisms and a therapeutic target for HMSN-P.